To serve God and Wal-Mart : - Moreton, Bethany. (Harvard University Press, 2009)
This extraordinary biography of Wal-Mart's world shows how a Christian pro-business movement grew from the bottom up as well as the top down, bolstering an economic vision that sanctifies corporate globalization